Control system of electron linac LU-40 - Akchurin, Yu.I.; Boriskin, V.N.; Gurin, V.A.; Demidov, N.V.; Yeran, L.V.; Ivahnenko, M.V.; Nescheret, S.F.; Savchenko, A.N.; Sarvilov, A.A.; Tatanov, V.I.; Tsebenko, G.N. (Вопросы атомной науки и техники, 2006)
The reconstruction of a two-section electron LU-40 linac was finished in 2004. The accelerator consists of two accelerating sections and an injector, the latter includes a diode electron gun, a klystron type buncher and an accelerating cavity. Pulse current at the accelerator exit is up to 200 µA, the beam energy is up to 100 MeV.